Behaviour and strength of screw connections in cold-formed steel structures - Sapiee, Siti Fairuz Binti (Curtin University, 2013)
Self-drilling screws are the primary means of fastening cold-formed steel members in cold-formed thin-gauge steel construction. This study was carried out to investigate the behaviour and strength of single-shear connections formed with self-drilling screws. The influences of the number of screws, screw spacing and screw patterns on the strength of self-drilling screw connections were determined. It was found that the numbers of screws and screw spacing affect the performance of the screw connection significantly as compared to screw patterns.